CLONING AND EXPRESSION OF LEISHMANOLYSIN GENE FROM LEISHMANIA MAJOR IN PRIMATE CELL LINES (Journal of Sciences, Islamic Republic of Iran)
Leishmanolysin is a worldwide disease that is caused by different species of the genus Leishmania. Leishmanolysin, One of the genes expressed by Leishmania, appears to be an ideal candidate for genetic vaccination. In this study, a full length sequence, which encodes Leishmanolysin functionally critical regions (amino acids 100-579), was cloned from a Leishmania strain endemic to Iran. Analysis by restriction enzyme digestion and DNA sequencing in pUC 19 based T-Vector showed that the cloned gene contained the conserved segments of the Leishmanolysin. The identified segments in predicted protein sequence of our clone contained the important domains that have been known to function at the attachment and internalization steps of the parasite life cycle. The cloned gene was expressed in human transformed muscle (Rhabdomyosarcoma TE671/RD) and African green monkey epithelial (COS-7) cell lines under cytomegalovirus (CMV) promoter, and the expressed protein was detected by enzyme linked immunosorbent assay. Thus the cloned gene may be used as an active component of a naked-DNA vaccine against Leishmaniasis in the geographic areas endemic to this parasite.